Central nervous system prostaglandin endoperoxide synthase-1 and −2 responses to oestradiol and cerebral hypoperfusion in late-gestation fetal sheep - Wood, Charles E (Blackwell Science Inc, 2003)
Previous work in this laboratory has demonstrated that cerebral hypoperfusion increases the expression of prostaglandin endoperoxide synthase-2 (PGHS-2) in ovine fetal brain regions. Endogenously produced prostaglandins, in turn, partially mediate the fetal hypothalamus- pituitary-adrenal (HPA) axis response to arterial hypotension. In separate experiments, we have found that oestradiol stimulates fetal HPA axis activity. The present experiments were designed to test the hypothesis that oestradiol increases the expression of PGHS isoforms, and that oestradiol augments the PGHS response to cerebral hypoperfusion. Sixteen fetal sheep of known gestational ages (124–128 days' gestation at the time of study) were subjected to chronic catheterization and implantation of extravascular occluder around the brachiocephalic artery. Eight fetuses were subjected to subcutaneous implantation of a pellet containing 17β-oestradiol (release rate 5 mg (21 days)(−1)). Brachiocephalic occlusion (BCO) stimulated adrenocorticotropin (ACTH), cortisol and arginine vasopressin (AVP) secretion, responses that were augmented by oestradiol. One hour after the beginning of a 10 min period of BCO, PGHS-1 mRNA was increased in fetal brainstem and hypothalamus, and PGHS-2 mRNA was increased in fetal brainstem. Oestradiol, by itself, increased the abundance of PGHS-2 mRNA in brainstem and cerebellum, and augmented the PGHS-2 mRNA response to BCO in brainstem. In contrast, oestradiol had no significant effect on the abundance of PGHS-1 mRNA in any brain region. PGHS-1 and PGHS-2 protein levels did not reflect the changes in the respective mRNAs. The abundance of both proteins was increased in cerebral cortex in response to BCO, and the abundance of PGHS-2 protein was increased by both oestradiol and BCO in the hippocampus. The results of this study confirm and extend the results of our previous studies, demonstrating an effect of cerebral hypoperfusion on the expression of both isoforms of PGHS. We conclude that oestradiol increases the expression of PGHS-2 in specific fetal brain regions, and that there is an interaction between oestradiol and BCO in the control of PGHS-2 expression in the fetal brainstem. We expect that at later time-points, the changes in mRNA would be followed by similar changes in enzyme abundance at the protein level. We speculate that at least a part of the effect of oestradiol on fetal HPA axis function is mediated by an interaction between oestradiol and prostaglandin biosynthesis in the fetal brain.